Enhancing Reflective Depth through Structured Video Mentoring in Indonesian Teacher Preparation Programs - Chisbiyah, Lismi Animatul; Hidayati, Laili (Indonesian Scientific Publication, 2025)
Reflective practice is crucial for pre-service teachers (PSTs) because it integrates theory and practice. Through reflection, PSTs can analyze their experiences, identify improvement areas, and strengthen pedagogical skills. Using a quasi-experimental mixed-methods design, 240 PSTs from three Indonesian teacher education institutions were divided into two groups: video-based mentoring and conventional mentoring. Reflective growth was measured using the Reflective Thinking Questionnaire (RTQ), Groningen Reflection Ability Scale (GRAS), and coded reflective journals. Mediation analysis assessed the role of mentoring quality using the METPI instrument. Thematic analysis of journals and interviews complemented the quantitative findings. PSTs in the video-supported mentoring group showed significantly higher post-test scores in both RTQ and GRAS compared to the control group. Mediation analysis confirmed that mentoring quality significantly predicted reflective depth. Qualitative data revealed common themes such as increased self-awareness, emotional resilience, and a refined teaching philosophy. The study confirms the value of modeling, coaching, and fading in mentoring, and demonstrates that video analysis supports deeper metacognitive engagement. National mentoring frameworks such as PPG and Kampus Mengajar offer strong infrastructure for scaling these practices. Nevertheless, challenges related to technological access and mentor training require systemic policy responses. Video-based mentoring enhances reflective thinking and supports the professional identity formation of PSTs. This model offers a scalable and theoretically sound strategy for improving teacher education quality in Indonesia and similar contexts. Further research should investigate long-term outcomes and implementation models across diverse institutions.